Genetic and Adverse Health Outcome Associations with Treatment Resistant Hypertension in GenHAT - Amy I. Lynch; Marguerite R. Irvin; Barry R. Davis; Charles E. Ford; John H. Eckfeldt; Donna K. Arnett (International Journal of Hypertension)
Treatment resistant hypertension (TRH) is defined as uncontrolled hypertension (HTN) despite the use of ≥3 antihypertensive medication classes or controlled HTN while treated with ≥4 antihypertensive medication classes. Risk factors for TRH include increasing age, diminished kidney function, higher body mass index, diabetes, and African American (AA) race. Importantly, previous studies suggest a genetic role in TRH, although the genetics of TRH are largely understudied. With 2203 treatment resistant cases and 2354 treatment responsive controls (36% AA) from the Genetics of Hypertension Associated Treatment Study (GenHAT), we assessed the association of 78 candidate gene polymorphisms with TRH status using logistic regression. After stratifying by race and adjusting for potential confounders, there were 2 genetic variants in the AGT gene (rs699, rs5051) statistically significantly associated with TRH among white participants. The Met allele of rs699 and the G allele of rs5051 were positively associated with TRH: OR=1.27 (1.12–1.44), P=0.0001, and OR=1.36 (1.20–1.53), P<0.0001, respectively. There was no similar association among AA participants (race interaction P=0.0004 for rs699 and P=0.0001 for rs5051). This research contributes to our understanding of the genetic basis of TRH, and further genetic studies of TRH may help reach the goal of better clinical outcomes for hypertensive patients.